1973
DOI: 10.1128/iai.8.2.151-155.1973
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Influence of Steroids on Viral Infection in Mice

Abstract: Certain steroids have been reported to enhance experimental viral infections, whereas others have little or no effect. Interference with the interferon system has been suggested as a possible mechanism for the viral infection-enhancing (VIE) activity of hormones. In the present study, steroids (prednisolone, progesterone, testosterone) which had no effect on MM virus infection demonstrated VIE activity against Mayaro virus infection. It is suggested that the VIE activity of a hormone may be dependent on the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Reproductive hormones and/or cortisone have been suggested to influence or to be influenced by several viral infections (Giron et al., 1973; Jones and Ambali, 1987; Al‐Afaleq, 1998). For example, Giron et al. (1973) studied the effects of certain steroids on the replication of mice encephalomyocarditis (MM) and Mayaro viruses in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive hormones and/or cortisone have been suggested to influence or to be influenced by several viral infections (Giron et al., 1973; Jones and Ambali, 1987; Al‐Afaleq, 1998). For example, Giron et al. (1973) studied the effects of certain steroids on the replication of mice encephalomyocarditis (MM) and Mayaro viruses in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Cortisone has been shown to enhance the replication of a number of animal viruses (6). As an extension of this phenomenon, the in vivo effects of other steroid hormones on virus replication have been examined (3,4). The results indicated that treatment of animals with estrone, cortisone, or hydrocortisone increased the susceptibility of animals to MM virus, an RNA virus.…”
mentioning
confidence: 99%